Idiomatic Expressions Analysis in Joker Movie - Annas Rozikin; Kasmaini Kasmaini; Azhar Aziz Lubis (Universitas Bengkulu, 2021)
This research aims to find out the types of idiomatic expressions and to identify the patterns of idiomatic expressions in the Joker movie. This research employed a descriptive qualitative method. In collecting the data, this research used a classification form, documentation, and monolingual dictionaries. The result showed that there were 4 types of idiomatic expressions found in the Joker movie; proverbs, clichés, fixed statements, and slang. The other types of idiomatic expressions such as simile, binomial, and other language were absent from the Joker movie. Moreover, the researcher identified the patterns of the idiomatic expressions in the Joker movie were; noun phrases, transitive verb phrases, verbal phrases, prepositional phrases, pair of words, and sentence pattern. The other patterns of idiomatic expressions such as be + prepositional phrases and alliterative comparison were not consisted in the Joker movie.